Challenges and Solutions for Existing Internet Networks in Afghanistan - Rahmatzai, Sibghatullah (Journal of Natural Sciences – Kabul University, 2024)
This research paper addresses the existing challenges in internet-related networks and explores suitable solutions for Afghanistan. The number of devices connected to the Internet and adopting new and emerging technologies—such as cloud computing, triple play services, Internet Protocol television (IPTV), and Voice over Internet Protocol (VoIP)—have significantly increased. In Afghanistan, these services are primarily offered through Digital Subscriber Line (DSL), wireless, and occasionally fiber optic networks. However, these networks lack the capacity to deliver high-bandwidth information over long distances, resulting in bandwidth bottlenecks and suboptimal service delivery. The research findings suggest that to effectively utilize new and emerging technologies, developing Gigabit Passive Optical Network (GPON)-based Fiber To Home (FTTH) networks is essential and provides a logical solution.